2008
DOI: 10.1177/0961203307085251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rituximab on clinical and laboratory features of antiphospholipid syndrome: a case report and a review of literature

Abstract: Antiphospholipid syndrome (APS) is an autoimmune disorder characterized by a hypercoagulable state related to persistently elevated levels of antiphospholipid antibodies (aPL). Current treatment for APS is only partially effective and new therapies are strongly needed. We report on a case of a 50 years old man with APS who suffered from recurrent thromboembolic episodes despite conventional anticoagulant treatment. Eight years after the first thrombotic manifestation he was diagnosed with a large B cell non-Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 14 publications
1
48
0
5
Order By: Relevance
“…Despite these results, RTX continues to be widely used 'off-label' for treatment resistant SLE. RTX use has also been reported in APS, mainly in severe cases with thrombocytopenia or autoimmune haemolytic anemia [41] and in APS patients resistant to standard therapy [42,43]. Erre and co-workers described 12 patients with primary and SLE-associated APS who were treated with RTX [42].…”
Section: New Oral Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these results, RTX continues to be widely used 'off-label' for treatment resistant SLE. RTX use has also been reported in APS, mainly in severe cases with thrombocytopenia or autoimmune haemolytic anemia [41] and in APS patients resistant to standard therapy [42,43]. Erre and co-workers described 12 patients with primary and SLE-associated APS who were treated with RTX [42].…”
Section: New Oral Anticoagulantsmentioning
confidence: 99%
“…RTX use has also been reported in APS, mainly in severe cases with thrombocytopenia or autoimmune haemolytic anemia [41] and in APS patients resistant to standard therapy [42,43]. Erre and co-workers described 12 patients with primary and SLE-associated APS who were treated with RTX [42]. RTX has also been shown to be an effective therapeutic option for life-threatening Catastrophic APS in a small number of patients [44].…”
Section: New Oral Anticoagulantsmentioning
confidence: 99%
“…In the absence of clinical improvement, other therapies should be provided: cyclophosphamide in SLE flares, prostacyclin or fibrinolytics or defibrotide. In CAPS patients with severe thrombocytopenia resistant to other forms of treatment, the administration of rituximab may be useful, as the direct inhibition of B-lymphocytes contributes to the decrease of the aPLs titre and the subsequent platelet activation (Erre et al, 2008). Finally, the objectives to be aggressively pursued in the management of CAPS are essentially four: 1 -addressing the triggering factors (adoption of antibiotic therapy in the event of infection and surgical toilet of the infection sources), 2 -maintenance of effective anticoagulation, also when CAPS is associated with thrombocytopenia, 3 -suppression and/or removal of cytokine excess, 4 -adoption of intensive care measures when necessary.…”
Section: Treatmentmentioning
confidence: 99%
“…Rituximab has been successfully used in case reports of patients with aPL and auto-immune mediated thrombocytopenia and hemolytic anemia. A systematic review of the off-label use of rituximab in APS revealed the higher rate of therapeutic response in patients with APS (92%) [193] and an increasing number of similar case reports clearly indicates the need for clinical trials to evaluate the effect of rituximab in the treatment of resistant APS. Currently Erkan et al are conducting a RITAPS open-label Phase II trial using Rituximab to study patients who are aPL positive and resistant to conventional anticoagulation (Clinical trials.gov Identifier: NCT00537290).…”
Section: B Hydroxychloroquinementioning
confidence: 99%